CLIFF-LAMNET Summer School Course - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
The new Latin America Greenhouse gas Mitigation Research Network Network (LAMNET) invited students from Latin American countries, currently enrolled in PhD programs, to attend a short course on greenhouse gas mitigation and also to conduct greenhouse gas measurements in livestock and rice production systems. During the course, students learned approaches used in the Standard Assessment of Mitigation Potential and Livelihoods in Smallholder Systems (SAMPLES) research program to evaluate options for reducing greenhouse gas emissions from rice and livestock systems.